2015
DOI: 10.12955/cbup.v4.832
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Health – Evaluation of the Locus of Control Over Health

Abstract: Health is a basic prerequisite for the existence and operation of values. Health care enables people to protect or restore health throughout their lives, from birth to death, in accordance with applicable legislation. This paper aims to identify the importance of assessing a locus of control over health using the scale measuring tool, Multidimensional Health Locus of Control (MHCL). In total, 100 respondents participated in the survey, with an average age of 42 years. Statistical analyses were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Further, Adame et al [ 19 ] reported that health was significantly related to the amount of exercise and the IHLC. Other studies have shown that wellness is affected by having an IHLC [ 20 ]. As such, the preceding study reported meaningful results on the relationship between sports participation, health control and care, and wellness [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Adame et al [ 19 ] reported that health was significantly related to the amount of exercise and the IHLC. Other studies have shown that wellness is affected by having an IHLC [ 20 ]. As such, the preceding study reported meaningful results on the relationship between sports participation, health control and care, and wellness [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that wellness is affected by having an IHLC [ 20 ]. As such, the preceding study reported meaningful results on the relationship between sports participation, health control and care, and wellness [ 18 , 19 , 20 ]. However, most studies have failed to examine the relationship among all variables comprehensively.…”
Section: Introductionmentioning
confidence: 99%